Takhrij and Syarah Hadith of Agrotechnology Benefits of al-Habbah as-Sauda Plants in Medicine - Ulfah Mardhiyah Khairunnisa; Wahyudin Darmalaksana; Ilim Abdul Halim; Dikayani Dikayani (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad concerning al-Habbah as-Sauda (black cumin). This research method is qualitative through the takhrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this study were to find out what are the benefits of the black cumin plant in medicine. Takhrij and syarah regarding the benefits of the al-Habbah as-Sauda (black cumin) plant in medicine have many benefits contained in it. This research recommends that it can be a policy consideration.